Hemodynamic responses during inspiratory muscle exercise in healthy young adults - Leila Dal Poggetto Moreira; Lilian Pinto da Silva; Vinícius Faria Weiss; Rita de Cássia Sene; Pedro Augusto de Carvalho Mira; Patrícia Fernandes Trevizan; Mateus Camaroti Laterza; Daniel Godoy Martinez (Universidade de São Paulo, 2023)
ABSTRACT The literature on hemodynamic responses during inspiratory muscle exercise (IME) lacks a consensus. To evaluate and compare hemodynamic responses during an IME session with and without resistive load, 15 sedentary men were subjected to two randomized IME sessions: one with 40% of maximal inspiratory pressure (IME 40%) and another without a resistive load (Sham), both of which were performed for two minutes over eight sessions with one-minute intervals. Systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure (MBP), total peripheral resistance (TPR), stroke volume (SV), cardiac output (CO), and heart rate (HR) were measured by infrared digital photoplethysmography during five basal minutes and during the IME sessions. One-way analysis of variance and the Student's t test for paired data were used to analyze hemodynamic response and delta values between sessions. Effect size was evaluated by Cohen's D. A 5% significance level was adopted. SBP responses (sham: ∆−1±2 vs. 40%: ∆−4±2mmHg, p=0.27), DBP (sham: ∆2±1 vs. 40%: ∆1±2mmHg, p=0.60) and MBP (sham: ∆2±1 vs. 40%: ∆0±2mmHg, p=0.28) were similar between sessions. HR increases were higher in the 40% IME session than in the sham session (sham: ∆9±2 vs. 40%: ∆3±2bpm, p=0.001). SV only decreased during the sham session but responses were similar between sessions (sham: ∆−2±2 vs. IME 40%: ∆−6±2ml, p=0.13). Both sessions did not change SBP, DBP, MBP, CO, and TPR, but we observed a greater increase in HR in the IME 40% session. Only the Sham session decreased SV.